Application of Local Species for Sustainable Phytoremediation: 10.32526/ennrj/21/20230125 - Ariyakanon, Naiyanan (Environment and Natural Resources Journal, 2023)
Phytoremediation is green technology based on the application of plants to remediate contaminated media. This paper reviews five species of local plants used for phytoremediation in Thailand: Pteris vittata L., Pityrogramma calomelanos L., Chrysopogon zizanioides L., Eichhornia crassipes (Mart.) Solms, and Pistia stratiotes L. For each plant, its pollutant removal efficiency and mechanism is reviewed. The main mechanisms of phytoremediation, such as phytoextraction, rhizofiltration, phytostabilization, phytodegradation, rhizodegradation, and phyto-volatilization, are concisely described. Screening local plants for phytoremediation is a cost-effective and easy to manage approach to derive suitable plants that are resistant to harmful environmental conditions. To be suitable, plants should have a fast growth rate, produce a large biomass yield, have a high tolerance to the toxic effects of the pollutants, and have a good capacity for pollutant uptake. Moreover, applying the proper species for each contaminant enhances the removal efficiency and supports sustainable phytoremediation.